Ocupaçoes e Rendimentos de Mulheres e Homens nas Areas Rurais no Nordeste do Brasil: uma análise para primeira década do século XXI - Staduto, Jefferson Andronio Ramundo (2017)
This paper aims to examine the occupation and income sources of women and men living in rural areas in the Northeast of Brazil, 2002 to 2009. The data were analyzed by descriptive statistics of the National Survey of Household Samples. The results show an increase of rural families in these areas, but a reduction of the family farmers. There was a drop in agricultural occupations and an increase of rural households' proletarization. The non-agricultural occupation was an important locus for women to generate income. The largest source of household income for men comes from agricultural occupations, and the social transfers are the largest sources to women